Recovery and Purification of Glycerine as By-product from Philippine Coconut Methyl Ester - Annabelle V. Briones (ASEAN Journal on Science and Technology for Development, 2019)
The study is about the recovery and purification of glycerine as a by-product from coconut methyl ester production in the Philippines. The aqueous layer produced from settling or phase splitting of the methyl ester after the transesterification process was subjected to various treatments like acidification, neutralization, concentration in vacuo in order to get back the crude glycerine. The crude glycerine obtained from the laboratory and scale-up process conformed with the specification set by the British standard for crude glycerine. The recovered glycerine is composed of: 84.92%, glycerine; 8.03%, ash; 4.72%, H20; 2.32%, MONG. Further distillation yielded a refined glycerine that meets with the specification set by USP. The average glycerine content of refined glycerine is 96.86%; ash, 0.06%; water, 1.10%, refractive index @ 20°C, 1.4696, specific gravity at 25°C, 1.296 g.